2002
DOI: 10.1089/108729002760220770
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Development of Respirable Antisense Therapeutics for Asthma

Abstract: Respirable antisense oligonucleotides (RASONs) represent a novel class of respiratory therapeutic molecules with the potential to specifically address the challenges posed by the successes of the Human Genome Program, namely, the need to rapidly identify the critical pulmonary disease-relevant drugable targets from the vast pool of 30,000-40,000 human genes and to discover and develop drugs that specifically attack these targets. We have shown that EPI-2010, a RASON targeting the adenosine A1 receptor, a G-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…External guide sequence technique, a novel approach, can specifically cleave target molecular by RNase P. Previous studies have demonstrated that RNA inactivation of targeted mRNA by EGS in vivo can be more effective than gene inactivation by conventional antisense DNA oligonucleotides [13,14], which have a different gene inactivation mechanism by endogenous RNase H [15,16]. Reduced off-site cleavage by EGS is also an advantage of EGS relative to RNAi and antisense technologies [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…External guide sequence technique, a novel approach, can specifically cleave target molecular by RNase P. Previous studies have demonstrated that RNA inactivation of targeted mRNA by EGS in vivo can be more effective than gene inactivation by conventional antisense DNA oligonucleotides [13,14], which have a different gene inactivation mechanism by endogenous RNase H [15,16]. Reduced off-site cleavage by EGS is also an advantage of EGS relative to RNAi and antisense technologies [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that EGS-based RNA inactivation of targeted mRNA in vivo can be orders of magnitude more effective than gene inactivation by conventional antisense DNA oligonucleotides [33,34] which have a different mechanism of action either by steric blocking of mRNA translation or by causing DNA/mRNA hybrid degradation by endogenous RNAse H [37,38]. If delivered effectively to pulmonary tissues, inhaled EGS ribozymes could have advantages over conventional antisense DNA oligonucleotides because of their ability to act as a co-catalyst for the ubiquitous RNAse P and the potential for a single EGS to recycle through multiple rounds of mRNA cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo absorption, tissue distribution, metabolism and excretion, efficacy and safety studies of respirable AS-ONs suggest that these antisense agents can be safely delivered to target respiratory tissues in low, but efficacious doses [17,18].…”
Section: Respirable Antisense Oligonucleotides (Rasons)mentioning
confidence: 99%